It Gets Worse - Lukowski, Len (feminists@law, 2014)
The launch of Subversive Property concluded with a performance of ‘It Gets Worse’ by Len Lukowski of the band FAGGOT. Audio and words for ‘It Gets Worse’ can be found at: http://faggottheband.bandcamp.com/track/it-gets-worse.